Isolation and Characterization of Bacteriophage which Infected Klebsiella pneumoniae - Muangman, Sunsiree; Gatedee, Jiraporn (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 4 (2022): October-December 2022, 2022)
Klebsiella pneumoniae is a clinically significant organism that has caused much public health concern. Due to the increasing prevalence of infections caused by multidrug-resistant K. pneumoniae , alternative therapies might be promising. The properties of host specificity, abundance in nature, and evolvability suggest bacteriophages might be a good candidate. In this study, we have isolated and characterized a lytic bacteriophage infecting K. pneumoniae , ØKN-2, which was isolated from wastewater. The transmission electron micrograph showed that ØKN-2 was classified as being in the Myoviridae family. Host-range determination revealed that ØKN-2 is specifically able to lyse 35.7% (5/14) of tested K. pneumoniae . Studies of the host range of different species showed that ØKN-2 unable to lyse other tested bacteria including Acinetobacter baumannii , Peudomonas aeruginosa , Protues mirabilis , Enterococcus faecalis , and Escherichia coli . Interestingly, ØKN-2 significantly reduced K. pneumoniae ATCC 700603 biofilm preformed in a dose dependent manner. Therefore, this study identified and tested bacteriophages that infect  K. pneumoniae and proved the effectiveness of ØKN-2 against biofilm and host-specific characteristics which indicates that they are beneficial in the development of treatments against K. pneumoniae infections. Keywords: K. pneumoniae , bacteriophages, biofilm, Myoviridae